The attraction of the Fabaceae family encyclopedia book: Educational development research - Salsabila Salsabila; Kaspul Kaspul; Muhammad Zaini (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
Critical thinking is one of the 4C skills students need to develop to compete in the 21st-century. Learning planning is focused not only on strategies and human resources, but also on learning resources. Learning resources integrated with the values of critical thinking skills need to be developed and tested. A learning resource that has the potential to be integrated with critical thinking values and generally has an attractive design is an encyclopedia. This study aims to analyze the content practicality or attractiveness of the Fabaceae family encyclopedia book. This study is an individual test in a series of educational development research (EDR) using the Tessmer formative evaluation research design. The data sources are three students enrolled in the Phanerogamae course. Data was collected using a readability questionnaire. Data analysis was carried out in a descriptive categorization manner. The results showed that the attractiveness of the Fabaceae family encyclopedia obtained a good category. This shows that the developed encyclopedia meets the standards and has an aesthetic value that can help students develop their critical thinking skills. The value is also supported by its user-friendly and visually appealing format. This encyclopedia still needs to be studied further in learning activities to analyze the value of its implementation. Abstrak. Berpikir kritis adalah salah satu keterampilan 4C yang perlu dikembangkan peserta didik agar mampu bersaing di abad 21. Perencanaan pembelajaran tidak hanya terfokus pada strategi dan sumber daya manusianya, melainkan juga sumber belajar. Sumber belajar yang terintegrasi dengan nilai-nilai keterampilan berpikir kritis perlu dikembangkan dan diuji. Sumber belajar yang berpotensi dapat diintegrasikan dengan nilai-nilai berpikir kritis dan pada umumnya memiliki desain yang menarik adalah ensiklopedia. Tujuan dari penelitian ini adalah menganalisis kepraktisan konten atau daya tarik buku ensiklopedia famili Fabaceae. Penelitian ini adalah uji perorangan dalam rangkaian penelitian pengembangan pendidikan (EDR) menggunakan desain penelitian evaluasi formatif Tessmer. Sumber data adalah tiga peserta didik yang terdaftar dalam kursus Phanerogamae. Data dikumpulkan dengan menggunakan angket keterbacaan. Analisis data dilakukan secara deskriptif kategorisasi. Hasil penelitian menunjukkan daya tarik ensiklopedia famili Fabaceae memperoleh kategori baik. Ini menunjukkan bahsa ensiklopendia yang dikembangkan memenuhi standar dan mempunyai nilai estetika yang dapat membantu siswa mengembangkan kemampuan berpikir kritisnya. Nilai tersebut juga didukung dengan formatnya yang ramah pengguna dan menarik secara visual. Ensiklopedia ini masih perlu dikaji lebih lanjut dalam kegiatan pembelajaran untuk menganalisis nilai implementasinya.